Pengalaman Peserta Didik dalam Pembelajaran Maharah Al-Kalam Berbasis Flashcard: Sebuah Studi Inkuiri Naratif - Sendy Ramadhani; Tubagus Kesa Purwasandy; Fadillah Prabowo (Tashfiyatuna: Jurnal Pendidikan Keislaman, 2023)
This study explores students’ experiences in learning Maharah Al-Kalam (Arabic speaking skills) through the use of flashcards among tenth-grade students of Madrasah Aliyah. Employing a qualitative approach with a narrative inquiry design, the research aims to understand learners’ meanings, motivations, and learning processes holistically. Data were collected through semi-structured in-depth interviews, participant observations, and documentation. Narrative thematic analysis was conducted through verbatim transcription, coding, pattern identification, and interpretation, supported by data triangulation. The findings reveal that flashcards enhance motivation, self-confidence, and Arabic speaking skills through engaging visualizations, ease of use, and support from teachers and peers. This study highlights the potential of flashcards as an innovative, interactive, and student-centered learning medium and provides practical recommendations for educators and instructional media developers.